The species‐spanning family of LPX‐motif harbouring effector proteins. (17th September 2018) - Norkowski, Stefanie; Schmidt, M. Alexander; Rüter, Christian
Abstract: The delivery of effector proteins into infected eukaryotic cells represents a key virulence feature of many microbial pathogens in order to derail essential cellular processes and effectively counter the host defence system. Although bacterial effectors are truly numerous and exhibit a wide range of biochemical activities, commonalities in terms of protein structure and function shared by many bacterial pathogens exist. Recent progress has shed light on a species‐spanning family of bacterial effectors containing an LPX repeat motif as a subtype of the leucine‐rich repeat superfamily, partially combined with a novel E3 ubiquitin ligase domain. This review highlights the immunomodulatory effects of LPX effector proteins, with particular emphasis on the exploitation of the host ubiquitin system.